Conspiracy - Gillott, Nick; Mandel, Loring; Pierson, Frank (HBO Home Video, 2001)
On January 20, 1942, 15 officials attended a conference at Wannsee on the outskirts of Berlin. Comprised of mid-ranking SS commanders and a variety of government ministers, the meeting was organized by SS Majaor Adolf Eichmann, under the direction of the ruthless and efficient Chief of Security Reinhard Heydrich. It was to be a polite conference with food, wine and some debate, but beneath this thin veneer of manner lay an evil intent. By the meeting's close, the fate of six million lives would be decided, and a terrible machine put into operation that would alter the shape of the world.